2017
DOI: 10.1002/cssc.201700261
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impact of Ionic Liquids: Recent Advances in (Eco)toxicology and (Bio)degradability

Abstract: This Review aims to integrate the most recent and pertinent data available on the (bio)degradability and toxicity of ionic liquids for global and critical analysis and on the conscious use of these compounds on a large scale thereafter. The integrated data will enable focus on the recognition of toxicophores and on the way the community has been dealing with them, with the aim to obtain greener and safer ionic liquids. Also, an update of the most recent biotic and abiotic methods developed to overcome some of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
120
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(127 citation statements)
references
References 239 publications
(342 reference statements)
1
120
0
Order By: Relevance
“…Between the two organic iodide catalysts, Bu 4 NI provedt ob ei ng eneral slightly less active than PPNI under the same conditions, but its higher solubility in the reaction mixture, lower cost, and lower toxicity [49] make it am ore attractive choice for upscaling. To achieve these results, it was crucial to carefully tune the amount of water relative to the epoxide, the nature of the anion and cation constituting the organic halide catalyst, and the remaining reaction conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between the two organic iodide catalysts, Bu 4 NI provedt ob ei ng eneral slightly less active than PPNI under the same conditions, but its higher solubility in the reaction mixture, lower cost, and lower toxicity [49] make it am ore attractive choice for upscaling. To achieve these results, it was crucial to carefully tune the amount of water relative to the epoxide, the nature of the anion and cation constituting the organic halide catalyst, and the remaining reaction conditions.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve these results, it was crucial to carefully tune the amount of water relative to the epoxide, the nature of the anion and cation constituting the organic halide catalyst, and the remaining reaction conditions. Between the two organic iodide catalysts, Bu 4 NI provedt ob ei ng eneral slightly less active than PPNI under the same conditions, but its higher solubility in the reaction mixture, lower cost, and lower toxicity [49] make it am ore attractive choice for upscaling.…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies have shown that ILs may be released into aquatic environments via effluent discharges and accidental spills and cause damage to aquatic organisms . For example, IL toxicity has been evaluated in microalgae, fish, and in Daphnia magna .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, sorption, biodegradability, and toxicity of ILs, as well as their degradation products, are of high importance for their impact and final fate in the environment (5,6 (3,4). In general, different test systems have shown different degrees of sensitivity to ILs indicating that the trophic level of test systems determines its susceptibility to ILs (7). Furthermore, all of the abovementioned studies indicate a strong relationship between ILs' chemical structure and degree of toxicity.…”
Section: Ionic Liquidsmentioning
confidence: 99%
“…These publications are related to ionic liquids' preparation; application (in chemistry, chemical engineering, and biotechnology); physical-chemical and biological characterisation; and impact on the environment (source: Web of Science). Since 2010, comprehensive studies on ionic liquids environmental impact including (bio) degradability and toxicity have been published (3)(4)(5)(6)(7). The purpose of this review is to present recent data on the biological effects of these compounds, with a special emphasis on their morphological and physiological changes in different biological systems, from bacteria to animal cells.…”
mentioning
confidence: 99%